Waterproof antibacterial polymer film material and preparation method thereof

By using multifunctional sheet block filler and fractal spherical reinforcement filler in bio-based polymer materials, combined with crosslinking agents, the problem of insufficient antibacterial and waterproofing properties of existing materials is solved, and the mechanical, waterproof and antibacterial properties of the materials are significantly improved.

CN119859326AInactive Publication Date: 2025-04-22HUNAN BOSHENG NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510348815.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The antibacterial and waterproof properties of existing bio-based polymer materials are poor, resulting in limited material service performance and life.

Method used

The multifunctional sheet block filler and fractal spherical reinforcement filler are combined, composed of glycine-modified molybdenum disulfide nanosheets, imidazolium salts, fractal nanocarriers, lignin nanoparticles and silver nitrate, respectively, and are filled in the matrix material of polyvinyl alcohol and corn starch, and under the action of crosslinking agent, the compatibility and interface combination of components are improved.

Benefits of technology

It significantly improves the mechanical properties, waterproof properties and antibacterial properties of the film materials, extends the service life, and optimizes the filling effect and interface combination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859326A_ABST
    Figure CN119859326A_ABST
Patent Text Reader

Abstract

The invention discloses a waterproof antibacterial polymer film material and a preparation method thereof, and relates to the technical field of film materials. The waterproof antibacterial polymer film material is composed of a multifunctional flaky filler, a fractal spherical reinforcing filler, a cross-linking agent, polyvinyl alcohol, corn starch and glycerin. According to the invention, a matrix material of polyvinyl alcohol and corn starch is jointly filled with a multifunctional flaky filler and a fractal spherical reinforcing filler, and under the further action of a cross-linking agent, the compatibility and dispersibility of double fillers in the matrix material are improved, the filling effect is optimized, and the interface bonding force of each component is enhanced; the mechanical property, the waterproof property and the antibacterial property of the film material are remarkably improved, and the service life is effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of film materials, and specifically refers to a waterproof and antibacterial polymer film material and a preparation method thereof. Background Art

[0002] Plastics made from petroleum are widely used in food packaging. They are low in cost and have the characteristics of being light and stable. However, petrochemical plastics cannot be naturally degraded in nature. Most plastics are directly landfilled or incinerated, causing environmental pollution and harming human health. Therefore, the application of environmentally friendly and degradable polymer materials is imperative and has become an important research direction in the field of packaging.

[0003] Bio-based degradable polymers have become the first choice to replace petroleum-based polymers due to their degradability, renewability, environmental friendliness and biocompatibility. Common bio-based degradable polymers include polyvinyl alcohol, polylactic acid, starch, protein, etc. Among them, polyvinyl alcohol and starch, as a renewable resource with good biocompatibility, are non-toxic, low-cost and abundant in reserves. The film material made from a mixture of the two not only has excellent environmental friendliness, but also has the potential for large-scale production.

[0004] The existing technology currently has the following problems:

[0005] Bio-based polymer materials have poor antibacterial and waterproof properties, which is not conducive to reducing food spoilage and loss, and cannot prevent material deformation and softening caused by moisture, thus limiting the material's performance and service life. Summary of the invention

[0006] In view of the above situation, in order to overcome the defects of the prior art, the present invention proposes a waterproof and antibacterial polymer film material, comprising the following components in parts by weight: 20-30 parts of multifunctional flake block filler, 10-20 parts of fractal spherical reinforcing filler, 10-15 parts of cross-linking agent, 30-40 parts of polyvinyl alcohol, 50-60 parts of corn starch, and 5-10 parts of glycerol.

[0007] The multifunctional sheet-like filler comprises the following components in parts by weight: 10-20 parts of glycine-modified molybdenum disulfide nanosheets and 30-40 parts of imidazolium salt.

[0008] The fractal spherical reinforcing filler comprises the following components in parts by weight: 10-20 parts of fractal nano-carriers, 5-10 parts of lignin nano-particles, and 8-10 parts of silver nitrate.

[0009] The method for preparing the multifunctional flake-shaped filler specifically comprises the following steps:

[0010] (1) 5.0 g of 1-allylimidazole and 11.2 g of bromododecane were added to a stoppered conical flask in sequence, and 30 mL of acetonitrile was added as the reaction solvent. The bottle mouth was plugged with a rubber stopper and wrapped with plastic wrap and aluminum foil. The conical flask was placed in a constant temperature magnetic stirrer at a temperature of 50-60°C and a rotation speed of 200-400 rpm for 24 hours. After the reaction was completed, it was allowed to stand and cooled to room temperature. The reaction solvent acetonitrile was then removed by rotary evaporation at a rotary evaporation temperature of 35°C for 0.5-1 hour. The solution is extracted and washed with ethyl acetate for 3-5 times, the lower layer of yellow liquid is taken, and the ethyl acetate is removed by rotary evaporation, the rotary evaporation temperature is 45°C, the rotary evaporation time is 0.5-1h, the viscous yellow liquid is collected, and it is dried. The long alkyl chain of the 1-allyl-3-dodecyl imidazolium salt prepared by this process is hydrophobic, can effectively repel moisture, and improve the waterproof performance of the material. The cation of the imidazolium salt can combine with the cell membrane of the microorganism, destroy its structure and cause cell death, thereby having a strong spectrum antibacterial effect, and obtaining the imidazolium salt;

[0011] (2) Add 20.0-30.0 g of glycine to 200 mL of distilled water, mix by ultrasonication for 20-30 min, then add molybdenum disulfide powder, stir at 400-500 rpm for 12-24 h, then ultrasonicate at 25 °C for 8-12 h, centrifuge, take the supernatant, add 5.0 g of glycine, ultrasonicate for 5-6 h, centrifuge for 60 min, replace the supernatant with distilled water every 10 min during centrifugation to better remove excess glycine in the solution, collect the precipitate and dry it. Glycine can disrupt the bacterial cell membrane. The permeability can be incorporated into the peptidoglycan of the bacterial cell wall to weaken its protective effect, thereby leading to cell death. The introduction of glycine also improves the interface bonding between molybdenum disulfide and the substrate, and enhances the mechanical properties of the film material. The use of glycine to peel off molybdenum disulfide makes the modified molybdenum disulfide nanosheets have better dispersibility and reduces the stacking phenomenon of nanosheets, thereby enhancing the mechanical properties, contact area with bacteria and antibacterial effect. However, the modification treatment of glycine also introduces hydrophilic groups, which is not conducive to maintaining the hydrophobic properties of molybdenum disulfide before modification, and obtains glycine-modified molybdenum disulfide nanosheets;

[0012] (3) dissolving the imidazolium salt described in step (1) in 20 mL of water, and then pouring the glycine-modified molybdenum disulfide nanosheets described in step S2 into the water, placing the mixture in a magnetic stirrer, controlling the temperature at 40-50° C., and stirring at 40-60 rpm for 1-2 h. The imidazolium salt is adsorbed on the glycine-modified molybdenum disulfide nanosheets through π-π stacking and hydrogen bonding to form a sheet-like structure, which not only encapsulates the hydrophilic groups introduced by glycine, presenting excellent hydrophobic properties, but also further enhances the antibacterial properties and mechanical properties. The mixture is then vacuum dried to obtain a multifunctional sheet-like filler.

[0013] Preferably, in step (2), the amount of molybdenum disulfide added is 1.0-2.0 g. Molybdenum disulfide can improve the barrier properties of materials such as polyvinyl alcohol and starch to water vapor, reduce the entry of moisture, and also improve the tensile strength and toughness of the material, making it more durable. The nanosheet structure can directly destroy the bacterial cell membrane, causing the cell contents to leak, thereby killing the bacteria.

[0014] The present invention also provides a method for preparing a waterproof and antibacterial polymer film material, which specifically comprises the following steps:

[0015] S1. Stir 90 mL of anhydrous ethanol, 30 mL of distilled water, 5 mL of ammonia water and 0.6 mL of ethylenediamine thoroughly, heat to 35-40°C, add 1.2 g of 3-aminophenol, 2.8 mL of formaldehyde and 5.2-5.5 mL of ethyl orthosilicate in sequence, stir vigorously at 8000-10000 rpm for 3-5 hours, centrifuge, collect the precipitate, wash it with ethanol 2-3 times, vacuum dry it, and then place it in a muffle furnace and calcine it at 500-550°C for 4-5 hours. Through this process, a silica nanoparticle with a fractal structure is prepared. The fractal rough surface can improve the adhesion of bacteria and has a larger surface area. As a carrier, it can load more active substances. In addition, the silica nanoparticles can fill the micropores and defects inside the material, improve the density and internal bonding force of the material, help to enhance the overall strength and toughness, and also help to reduce the entry of water to obtain a fractal nanocarrier;

[0016] S2, adding 1.0g of lignin to a eutectic of 100mL of water and tetrahydrofuran, wherein the volume ratio of water to tetrahydrofuran is 3:7, magnetic stirring for 0.5-1h, then dripping 40mL of deionized water into the lignin suspension at a rate of 2mL / min, stirring continuously for 3-4h, transferring to a dialysis bag, immersing the dialysis bag in excess deionized water to remove tetrahydrofuran, replacing deionized water every 12h, collecting the precipitate after 36h, and preparing nano-granular lignin by this process, with a small particle size but a large specific surface area, increasing the contact with other materials, improving the adsorption capacity, and obtaining lignin nanoparticles;

[0017] S3, grinding the fractal nanocarrier described in step S1 and placing it in a round-bottom flask, adding 80 mL of toluene, ultrasonically treating for 20-30 min, then placing it in an oil bath at 70-80°C, magnetically stirring for 20-30 min, quickly adding 0.1-0.5 mL of 3-aminopropyltriethoxysilane, reacting for 8-12 h, centrifuging, washing the product with ethanol, and obtaining a modified fractal nanocarrier, which is then dispersed in 30 mL of ultrapure water, ultrasonically treating for 10-30 min, adding the lignin nanoparticles described in step S2, magnetically stirring for 2-3 h, and finally adding silver nitrate, stirring at room temperature in the dark for 1-2 h, dropping 5 mL of a 2-6% by mass sodium borohydride aqueous solution to reduce the silver ions to form silver nanoparticles, centrifuging, washing, and vacuuming. Drying, the introduction of 3-aminopropyltriethoxysilane improves the surface activity and loading stability of the fractal nanocarrier, effectively improves the loading effect of lignin nanoparticles, and the addition of lignin nanoparticles further enhances the adsorption and binding ability of the fractal nanocarrier to silver ions, and can load more silver nanoparticles, thereby better improving the antibacterial performance, and the adsorption of lignin nanoparticles and silver nanoparticles by the modified fractal nanocarrier forms a rougher spherical surface, showing better waterproofness, wherein the phenolic hydroxyl group of lignin can assist in reducing silver ions into silver nanoparticles, and the lignin nanoparticles can also reduce the agglomeration of silica particles, which is conducive to uniform dispersion, and more fully exerts the improvement effect of the filler on the mechanical properties, thereby obtaining a fractal spherical reinforcing filler;

[0018] S4. Mix starch and sodium periodate, add to 100 mL of deionized water, adjust the pH to 2.5 with 0.4% hydrochloric acid solution, stir at 35-38°C for 5-6 hours, add 300 mL of anhydrous ethanol, stir evenly, centrifuge, take the precipitate, wash repeatedly with 75% ethanol solution until the pH is 7.0, then wash twice with distilled water, freeze-dry, the aldehyde group in the dialdehyde starch reacts with the hydroxyl group, amino group and other groups in the material to form a stable covalent bond, thereby improving the mechanical strength of the material, and at the same time, the presence of hydrophilic groups is reduced after cross-linking, and the water resistance and waterproofing are enhanced, and a cross-linking agent is obtained;

[0019] S5, polyvinyl alcohol and corn starch are mixed at a mixing speed of 60-80rpm and a mixing time of 20-30min, and then a multifunctional flake filler, a fractal spherical reinforcing filler described in step S3, a cross-linking agent described in step S4 and glycerol are added at a mixing speed of 80-100rpm and a mixing time of 20-30min, and then the mixture is fed into a twin-screw extruder granulator with a length-to-diameter ratio of 40:1, and granulated at a temperature of 110-120°C. After granulation, the granulated material is added into a single-screw film blowing machine with a length-to-diameter ratio of 40:1, and plasticized and extruded at a temperature of 100-110°C. The multifunctional flake-shaped filler provides a larger surface area and enhances the interface interaction, and the fractal spherical reinforcing filler fills the gap. The combination of the two optimizes the filling effect. The addition of the cross-linking agent can not only undergo nucleophilic addition with the multifunctional flake-shaped filler, but also form coordination cross-linking with the fractal spherical reinforcing filler, and can also cross-link with the hydroxyl groups in polyvinyl alcohol and starch, so that the filler is fully compatible and dispersed in the matrix, the interface bonding between the materials is more firm, and the defects are effectively reduced, thereby significantly improving the mechanical properties, waterproof properties and antibacterial properties, and obtaining a waterproof and antibacterial polymer film material;

[0020] Preferably, in step S3, the amount of silver nitrate added is 8.0-10.0 mg. Silver nitrate has a spectrum of antibacterial properties, and the antibacterial effect is long-lasting and effective. It can exert a strong antibacterial effect at a low concentration, and has important application value in antibacterial materials;

[0021] Preferably, in step S4, the amount of starch added is 4.0-5.0 g, and the amount of sodium periodate added is 4.0-5.0 g, and dialdehyde starch is produced by selectively oxidizing the vicinal diol structure in the starch by periodate.

[0022] The beneficial effects achieved by the present invention are as follows:

[0023] The present invention combines multifunctional sheet-shaped fillers and fractal spherical reinforcing fillers in a matrix material of polyvinyl alcohol and corn starch, and under the further action of a cross-linking agent, improves the compatibility and dispersibility of the dual fillers in the matrix material, optimizes the filling effect, enhances the interface bonding force of each component, significantly improves the mechanical properties, waterproof properties and antibacterial properties of the film material, and effectively prolongs the service life; in the multifunctional sheet-shaped filler, glycine is first used to strip and modify molybdenum disulfide, so that the modified molybdenum disulfide nanosheets have better dispersibility, reduce the stacking phenomenon, and enhance the mechanical properties of the nanosheets , contact area with bacteria and antibacterial effect, and then adsorb the imidazolium salt on the glycine-modified molybdenum disulfide nanosheets to form an electrostatic assembly of the nanosheets, which not only encapsulates the hydrophilic groups introduced by glycine, presents excellent hydrophobic properties, and can reduce the moisture deformation phenomenon of the material, but also enhances the antibacterial and mechanical properties of the flake-shaped filler through electrostatic action; in the fractal spherical reinforcing filler, through the activation of 3-aminopropyltriethoxysilane and lignin nanoparticles, the fractal nanocarrier can adsorb and bind more silver nanoparticles, which is beneficial to improve the antibacterial performance, and at the same time, the modified fractal nanocarrier The adsorption of lignin nanoparticles and silver nanoparticles by the body also makes the spherical surface rougher, thus showing better waterproofness. Among them, lignin nanoparticles can also reduce the agglomeration of silica particles, which is beneficial to the uniformity of dispersion in the matrix material and more fully exerts the effect of fillers on improving mechanical properties; multifunctional flake fillers provide a larger surface area, and fractal spherical reinforcing fillers fill the existing gaps. The combined use of double fillers optimizes the filling effect, which is beneficial to improving the comprehensiveness, efficiency and effectiveness of the mechanical properties, waterproof properties and antibacterial properties of the film material. The addition of cross-linking agent, The dispersion stability and density of each component are further improved, and the interface bonding between the materials is more firm and tight, which is helpful to absorb and disperse the impact force, reduce the damage to the material by stress concentration, and also reduce the space for bacterial growth and the entry of moisture, thereby significantly improving the mechanical properties, waterproof properties and antibacterial properties of the film material and extending the service life; the present invention uses multifunctional flake block fillers, fractal spherical reinforcing fillers, cross-linking agents, polyvinyl alcohol, corn starch and glycerol to make a waterproof and antibacterial polymer film material, which has excellent waterproof and antibacterial properties, effectively reduces material deformation, and extends service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope image of the waterproof and antibacterial polymer film material prepared in Example 1 of the present invention;

[0025] Figure 2 The mechanical properties of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0026] Figure 3The water vapor transmission rate results of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0027] Figure 4 It is a graph showing the antibacterial rate results of Examples 1-4 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0030] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0031] Example 1

[0032] This embodiment proposes a waterproof and antibacterial polymer film material, which includes the following components in parts by weight: 30 parts of multifunctional flake-shaped filler, 20 parts of fractal spherical reinforcing filler, 15 parts of cross-linking agent, 40 parts of polyvinyl alcohol, 60 parts of corn starch, and 10 parts of glycerol.

[0033] The multifunctional sheet-like filler comprises the following components in parts by weight: 20 parts of glycine-modified molybdenum disulfide nanosheets and 40 parts of imidazolium salt.

[0034] The fractal spherical reinforcing filler comprises the following components in parts by weight: 20 parts of fractal nano-carriers, 10 parts of lignin nano-particles, and 10 parts of silver nitrate.

[0035] The preparation method of the multifunctional sheet-like filler specifically comprises the following steps:

[0036] (1) 5.0 g of 1-allylimidazole and 11.2 g of bromododecane were added to a stoppered conical flask in sequence, and 30 mL of acetonitrile was added as the reaction solvent. The bottle mouth was plugged with a rubber stopper and wrapped with plastic wrap and aluminum foil. The conical flask was placed in a constant temperature magnetic stirrer at 60 ° C and 400 rpm for 24 h. After the reaction was completed, it was allowed to stand and cooled to room temperature. The reaction solvent acetonitrile was removed by rotary evaporation at 35 ° C for 1 h, and then acetic acid was added. The solution was extracted and washed with ethyl ester for 5 times, the lower layer of yellow liquid was taken, and the ethyl acetate was removed by rotary evaporation. The rotary evaporation temperature was 45°C and the rotary evaporation time was 1 hour. The viscous yellow liquid was collected and dried. The long alkyl chain of 1-allyl-3-dodecyl imidazolium salt prepared by this process was hydrophobic and could effectively repel water and improve the waterproof performance of the material. The cation of the imidazolium salt could combine with the cell membrane of microorganisms, destroy its structure and cause cell death, thereby having a strong spectrum antibacterial effect to obtain the imidazolium salt.

[0037] (2) Add 30.0 g of glycine to 200 mL of distilled water and mix them ultrasonically for 30 min. Then add molybdenum disulfide powder. The amount of molybdenum disulfide added is 2.0 g. Molybdenum disulfide can improve the barrier properties of materials such as polyvinyl alcohol and starch to water vapor, reduce the entry of water, and improve the tensile strength and toughness of the material, making it more durable. The nanosheet structure can directly destroy the bacterial cell membrane, causing the cell contents to leak, thereby killing the bacteria. Stir at 500 rpm for 24 h, then ultrasonically treat at 25 °C for 12 h, centrifuge, take the supernatant, add 5.0 g of glycine, ultrasonically treat for 6 h, and centrifuge for 60 min. During the centrifugation, replace it with distilled water every 10 min. The supernatant can better remove excess glycine in the solution, collect the precipitate and dry it. Glycine can disrupt the permeability of bacterial cell membranes and can be incorporated into the peptidoglycan of bacterial cell walls to weaken its protective effect, thereby leading to cell death. The introduction of glycine also improves the interface bonding between molybdenum disulfide and the substrate, enhances the mechanical properties of the film material, and uses glycine to peel off molybdenum disulfide, so that the modified molybdenum disulfide nanosheets have better dispersibility and reduce the stacking phenomenon of nanosheets, thereby enhancing the mechanical properties, contact area with bacteria and antibacterial effect. However, the modification treatment of glycine also introduces hydrophilic groups, which is not conducive to maintaining the hydrophobic properties of molybdenum disulfide before modification, and obtains glycine-modified molybdenum disulfide nanosheets;

[0038] (3) The imidazolium salt described in step (1) is dissolved in 20 mL of water, and then the glycine-modified molybdenum disulfide nanosheets described in step S2 are poured into the water. The mixture is placed in a magnetic stirrer, the temperature is controlled at 50°C, and the mixture is stirred at 60 rpm for 2 h. The imidazolium salt is adsorbed on the glycine-modified molybdenum disulfide nanosheets through π-π stacking and hydrogen bonding to form a sheet-like structure. The hydrophilic groups introduced by glycine are coated therein to exhibit excellent hydrophobic properties, and the antibacterial properties and mechanical properties are further enhanced. The mixture is then vacuum dried to obtain a multifunctional sheet-like filler.

[0039] This embodiment provides a method for preparing a waterproof and antibacterial polymer film material, which specifically includes the following steps:

[0040] S1. Stir 90 mL of anhydrous ethanol, 30 mL of distilled water, 5 mL of ammonia water and 0.6 mL of ethylenediamine thoroughly, heat to 40°C, add 1.2 g of 3-aminophenol, 2.8 mL of formaldehyde and 5.5 mL of ethyl orthosilicate in sequence, stir vigorously at 10,000 rpm for 5 h, centrifuge, collect the precipitate, wash it with ethanol 3 times, vacuum dry it, and then place it in a muffle furnace and calcine it at 550°C for 5 h. Through this process, a silica nanoparticle with a fractal structure is prepared. The fractal rough surface can improve the adhesion of bacteria and has a larger surface area. As a carrier, it can load more active substances. In addition, the silica nanoparticles can fill the micropores and defects inside the material, improve the density and internal bonding force of the material, help to enhance the overall strength and toughness, and also help to reduce the entry of water to obtain a fractal nanocarrier;

[0041] S2, adding 1.0g of lignin to a eutectic of 100mL of water and tetrahydrofuran, wherein the volume ratio of water to tetrahydrofuran is 3:7, magnetically stirring for 1h, then dripping 40mL of deionized water into the lignin suspension at a rate of 2mL / min, stirring continuously for 4h, transferring to a dialysis bag, immersing the dialysis bag in excess deionized water to remove tetrahydrofuran, replacing deionized water every 12h, collecting the precipitate after 36h, and preparing nano-granular lignin by this process, with a small particle size but a large specific surface area, increasing the contact with other materials, improving the adsorption capacity, and obtaining lignin nanoparticles;

[0042] S3, grind the fractal nanocarrier described in step S1 and put it into a round-bottom flask, add 80 mL of toluene, ultrasonically treat for 30 minutes, then place it in an oil bath at 80°C, magnetically stir for 30 minutes, quickly add 0.5 mL of 3-aminopropyltriethoxysilane, react for 12 hours, centrifuge, wash the product with ethanol, and obtain a modified fractal nanocarrier, which is then dispersed in 30 mL of ultrapure water, ultrasonically treated for 30 minutes, add the lignin nanoparticles described in step S2, magnetically stir for 3 hours, and finally add silver nitrate in an amount of 10.0 mg. Silver nitrate has spectral antibacterial properties, and the antibacterial effect is long-lasting and effective. It can exert a strong antibacterial effect at low concentrations and has important application value in antibacterial materials. Stir for 2 hours in the dark at room temperature, drop 5 mL of a 6% sodium borohydride aqueous solution, The silver ions are reduced to form silver nanoparticles, centrifuged, washed, and vacuum dried. The introduction of 3-aminopropyltriethoxysilane improves the surface activity and loading stability of the fractal nanocarrier, and effectively improves the loading effect of the lignin nanoparticles. The addition of lignin nanoparticles further enhances the adsorption and binding ability of the fractal nanocarrier to silver ions, and can load more silver nanoparticles, thereby better improving the antibacterial performance. The modified fractal nanocarrier adsorbs lignin nanoparticles and silver nanoparticles, forming a rougher spherical surface and showing better waterproofness. The phenolic hydroxyl group of lignin can assist in reducing silver ions to silver nanoparticles, and the lignin nanoparticles can also reduce the agglomeration of silica particles, which is conducive to uniform dispersion, and more fully exerts the improvement effect of the filler on the mechanical properties, thereby obtaining a fractal spherical reinforcing filler.

[0043] S4. Mix starch and sodium periodate, the amount of starch added is 5.0g, the amount of sodium periodate added is 5.0g, add them into 100mL deionized water, use 0.4% hydrochloric acid solution to adjust the pH to 2.5, stir at 38°C for 6h, then add 300mL of anhydrous ethanol, stir evenly, centrifuge, take the precipitate, wash repeatedly with 75% ethanol solution until the pH is 7.0, then wash twice with distilled water, freeze-dry, and selectively oxidize the vicinal diol structure in starch by periodate to produce dialdehyde starch. The aldehyde group in the dialdehyde starch reacts with the hydroxyl group, amino group and other groups in the material to form a stable covalent bond, thereby improving the mechanical strength of the material. At the same time, after cross-linking, the presence of hydrophilic groups is reduced, and the water resistance and waterproofness are enhanced to obtain a cross-linking agent;

[0044] S5, polyvinyl alcohol and corn starch are mixed at a mixing speed of 80 rpm for 30 min, and then the multifunctional flake filler, the fractal spherical reinforcing filler described in step S3, the cross-linking agent described in step S4 and glycerol are added at a mixing speed of 100 rpm for 30 min, and then the mixture is sent to a twin-screw extruder granulator with a length-to-diameter ratio of 40:1, and granulated at a temperature of 120°C. After the granulation is completed, the granulated material is added to a single-screw film blowing machine with a length-to-diameter ratio of 40:1, and plasticized extrusion, inflation treatment, cooling, and film blowing are performed in sequence at a temperature of 110°C. Rolling up, the multifunctional flake-like filler provides a larger surface area and enhances the interfacial interaction, and the fractal spherical reinforcing filler fills the gaps. The combination of the two optimizes the filling effect, and the addition of the cross-linking agent can not only undergo nucleophilic addition with the multifunctional flake-like filler, but also form coordination cross-linking with the fractal spherical reinforcing filler, and can also cross-link with the hydroxyl groups in polyvinyl alcohol and starch, so that the filler is fully compatible and dispersed in the matrix, the interface bonding between the materials is more firm, and defects are effectively reduced, thereby significantly improving the mechanical properties, waterproof properties and antibacterial properties, and obtaining a waterproof and antibacterial polymer film material.

[0045] In this embodiment, the prepared waterproof and antibacterial polymer film material was subjected to scanning electron microscopy to observe its microscopic morphology. Figure 1 This is a SEM image of the waterproof and antibacterial polymer film material prepared in Example 1 magnified 200 times, as shown Figure 1 The interface of the waterproof and antibacterial polymer film material prepared in this embodiment is tightly cross-linked and has a good filling effect.

[0046] Example 2

[0047] This embodiment provides a waterproof and antibacterial polymer film material, which includes the following components in parts by weight: 20 parts of multifunctional flake-shaped filler, 20 parts of fractal spherical reinforcing filler, 10 parts of cross-linking agent, 30 parts of polyvinyl alcohol, 50 parts of corn starch, and 5 parts of glycerol.

[0048] The multifunctional sheet-like filler comprises the following components in parts by weight: 10 parts of glycine-modified molybdenum disulfide nanosheets and 30 parts of imidazolium salt.

[0049] The fractal spherical reinforcing filler comprises the following components in parts by weight: 10 parts of fractal nano-carriers, 5 parts of lignin nano-particles, and 8 parts of silver nitrate.

[0050] The preparation method of the multifunctional sheet-like filler specifically comprises the following steps:

[0051] (1) 5.0 g of 1-allylimidazole and 11.2 g of bromododecane were added to a stoppered conical flask in sequence, and 30 mL of acetonitrile was added as the reaction solvent. The bottle mouth was plugged with a rubber stopper and wrapped with plastic wrap and aluminum foil. The conical flask was placed in a constant temperature magnetic stirrer at 50 °C and 200 rpm for 24 h. After the reaction was completed, the mixture was allowed to stand and cooled to room temperature. The reaction solvent acetonitrile was then removed by rotary evaporation at 35 °C for 0.5 h. Then, acetic acid was added to the mixture. The solution was extracted and washed with ethyl ester for 3 times, the lower layer of yellow liquid was taken, and the ethyl acetate was removed by rotary evaporation. The rotary evaporation temperature was 45°C and the rotary evaporation time was 0.5h. The viscous yellow liquid was collected and dried. The long alkyl chain of 1-allyl-3-dodecyl imidazolium salt prepared by this process was hydrophobic and could effectively repel moisture and improve the waterproof performance of the material. The cation of the imidazolium salt could combine with the cell membrane of microorganisms, destroy its structure and cause cell death, thereby having a strong spectrum antibacterial effect to obtain the imidazolium salt.

[0052] (2) Add 20.0 g of glycine to 200 mL of distilled water and mix them ultrasonically for 20 min. Then add molybdenum disulfide powder. The amount of molybdenum disulfide added is 1.0 g. Molybdenum disulfide can improve the barrier properties of materials such as polyvinyl alcohol and starch to water vapor, reduce the entry of water, and improve the tensile strength and toughness of the material, making it more durable. The nanosheet structure can directly destroy the bacterial cell membrane, causing the cell contents to leak, thereby killing the bacteria. Stir at 400 rpm for 12 h, then ultrasonically treat at 25 °C for 8 h, centrifuge, take the supernatant, add 5.0 g of glycine, ultrasonically treat for 5 h, and centrifuge for 60 min. During the centrifugation, replace it with distilled water every 10 min. The supernatant can better remove excess glycine in the solution, collect the precipitate and dry it. Glycine can disrupt the permeability of bacterial cell membranes and can be incorporated into the peptidoglycan of bacterial cell walls to weaken its protective effect, thereby leading to cell death. The introduction of glycine also improves the interface bonding between molybdenum disulfide and the substrate, enhances the mechanical properties of the film material, and uses glycine to peel off molybdenum disulfide, so that the modified molybdenum disulfide nanosheets have better dispersibility and reduce the stacking phenomenon of nanosheets, thereby enhancing the mechanical properties, contact area with bacteria and antibacterial effect. However, the modification treatment of glycine also introduces hydrophilic groups, which is not conducive to maintaining the hydrophobic properties of molybdenum disulfide before modification, and obtains glycine-modified molybdenum disulfide nanosheets;

[0053] (3) The imidazolium salt described in step (1) is dissolved in 20 mL of water, and then the glycine-modified molybdenum disulfide nanosheets described in step S2 are poured into the water. The mixture is placed in a magnetic stirrer, the temperature is controlled at 40°C, and the mixture is stirred at 40 rpm for 1 hour. The imidazolium salt is adsorbed on the glycine-modified molybdenum disulfide nanosheets through π-π stacking and hydrogen bonding to form a sheet-like structure. The hydrophilic groups introduced by glycine are coated therein to exhibit excellent hydrophobic properties, and the antibacterial properties and mechanical properties are further enhanced. The mixture is then vacuum dried to obtain a multifunctional sheet-like filler.

[0054] This embodiment provides a method for preparing a waterproof and antibacterial polymer film material, which specifically includes the following steps:

[0055] S1. Stir 90 mL of anhydrous ethanol, 30 mL of distilled water, 5 mL of ammonia water and 0.6 mL of ethylenediamine thoroughly, heat to 35-40°C, add 1.2 g of 3-aminophenol, 2.8 mL of formaldehyde and 5.2 mL of ethyl orthosilicate in sequence, stir vigorously at 8000 rpm for 3 hours, centrifuge, collect the precipitate, wash it twice with ethanol, vacuum dry it, and then place it in a muffle furnace and calcine it at 500°C for 4 hours. Through this process, a silica nanoparticle with a fractal structure is prepared. The fractal rough surface can improve the adhesion of bacteria and has a larger surface area. As a carrier, it can load more active substances. In addition, the silica nanoparticles can fill the micropores and defects inside the material, improve the density and internal bonding force of the material, help to enhance the overall strength and toughness, and also help to reduce the entry of water to obtain a fractal nanocarrier;

[0056] S2, adding 1.0g of lignin to a eutectic of 100mL of water and tetrahydrofuran, wherein the volume ratio of water to tetrahydrofuran is 3:7, magnetic stirring for 0.5h, then dripping 40mL of deionized water into the lignin suspension at a rate of 2mL / min, stirring continuously for 3h, transferring to a dialysis bag, immersing the dialysis bag in excess deionized water to remove tetrahydrofuran, replacing deionized water every 12h, collecting the precipitate after 36h, and preparing nano-granular lignin by this process, which has a small particle size but a large specific surface area, increases the contact with other materials, improves the adsorption capacity, and obtains lignin nanoparticles;

[0057] S3, grind the fractal nanocarrier described in step S1 and put it into a round-bottom flask, add 80 mL of toluene, ultrasonically treat for 20 minutes, then place it in an oil bath at 70°C, magnetically stir for 20 minutes, quickly add 0.1 mL of 3-aminopropyltriethoxysilane, react for 8 hours, centrifuge, wash the product with ethanol, and obtain a modified fractal nanocarrier, which is then dispersed in 30 mL of ultrapure water, ultrasonically treat for 10 minutes, add the lignin nanoparticles described in step S2, magnetically stir for 2 hours, and finally add silver nitrate in an amount of 8.0 mg. Silver nitrate has spectral antibacterial properties, and the antibacterial effect is long-lasting and effective. It can exert a strong antibacterial effect at low concentrations and has important application value in antibacterial materials. Stir in the dark at room temperature for 1 hour, drop 5 mL of a 2% sodium borohydride aqueous solution, and also The original silver ions form silver nanoparticles, which are centrifuged, washed, and vacuum dried. The introduction of 3-aminopropyltriethoxysilane improves the surface activity and loading stability of the fractal nanocarrier, and effectively improves the loading effect of the lignin nanoparticles. The addition of lignin nanoparticles further enhances the adsorption and binding ability of the fractal nanocarrier for silver ions, and can load more silver nanoparticles, thereby better improving the antibacterial performance. The modified fractal nanocarrier adsorbs lignin nanoparticles and silver nanoparticles, forming a rougher spherical surface and presenting better waterproofness. The phenolic hydroxyl group of lignin can assist in reducing silver ions into silver nanoparticles, and the lignin nanoparticles can also reduce the agglomeration of silica particles, which is conducive to uniform dispersion, and more fully exerts the improvement effect of the filler on the mechanical properties, thereby obtaining a fractal spherical reinforcing filler.

[0058] S4. Mix starch and sodium periodate, with the amount of starch added being 4.0 g and the amount of sodium periodate added being 5.0 g, add them into 100 mL of deionized water, adjust the pH to 2.5 with a 0.4% hydrochloric acid solution, stir at 35°C for 5 h, then add 300 mL of anhydrous ethanol, stir evenly, centrifuge, take the precipitate, wash repeatedly with a 75% ethanol solution until the pH is 7.0, then wash twice with distilled water, freeze-dry, and selectively oxidize the vicinal diol structure in the starch with periodate to produce dialdehyde starch. The aldehyde group in the dialdehyde starch reacts with the hydroxyl group, amino group and other groups in the material to form a stable covalent bond, thereby improving the mechanical strength of the material. At the same time, after cross-linking, the presence of hydrophilic groups is reduced, and the water resistance and waterproofness are enhanced, thereby obtaining a cross-linking agent;

[0059] S5, polyvinyl alcohol and corn starch are mixed at a mixing speed of 60 rpm and a mixing time of 20 min, and then a multifunctional flake filler, the fractal spherical reinforcing filler described in step S3, the cross-linking agent described in step S4 and glycerol are added at a mixing speed of 80 rpm and a mixing time of 20 min, and then the mixture is fed into a twin-screw extruder granulator with a length-to-diameter ratio of 40:1, and granulated at a temperature of 110°C. After the granulation is completed, the granulated material is added into a single-screw film blowing machine with a length-to-diameter ratio of 40:1, and plasticized, extruded, blown, cooled, and granulated at a temperature of 100°C in sequence. Rolling up, the multifunctional flake-like filler provides a larger surface area and enhances the interfacial interaction, and the fractal spherical reinforcing filler fills the gaps. The combination of the two optimizes the filling effect, and the addition of the cross-linking agent can not only undergo nucleophilic addition with the multifunctional flake-like filler, but also form coordination cross-linking with the fractal spherical reinforcing filler, and can also cross-link with the hydroxyl groups in polyvinyl alcohol and starch, so that the filler is fully compatible and dispersed in the matrix, the interface bonding between the materials is more firm, and defects are effectively reduced, thereby significantly improving the mechanical properties, waterproof properties and antibacterial properties, and obtaining a waterproof and antibacterial polymer film material.

[0060] Example 3

[0061] This embodiment provides a waterproof and antibacterial polymer film material, including the following components in parts by weight: 20 parts of multifunctional flake-shaped filler, 10 parts of fractal spherical reinforcing filler, 12.5 parts of cross-linking agent, 35 parts of polyvinyl alcohol, 55 parts of corn starch, and 7.5 parts of glycerol.

[0062] The multifunctional sheet-like filler comprises the following components in parts by weight: 15 parts of glycine-modified molybdenum disulfide nanosheets and 35 parts of imidazolium salt.

[0063] The fractal spherical reinforcing filler comprises the following components in parts by weight: 15 parts of fractal nano-carriers, 7.5 parts of lignin nano-particles, and 9 parts of silver nitrate.

[0064] The preparation method of the multifunctional sheet-like filler specifically comprises the following steps:

[0065] (1) 5.0 g of 1-allylimidazole and 11.2 g of bromododecane were added to a stoppered conical flask in sequence, and 30 mL of acetonitrile was added as the reaction solvent. The bottle mouth was plugged with a rubber stopper and wrapped with plastic wrap and aluminum foil. The conical flask was placed in a constant temperature magnetic stirrer at 55 °C and 300 rpm for 24 h. After the reaction was completed, it was allowed to stand and cooled to room temperature. The reaction solvent acetonitrile was then removed by rotary evaporation at a rotary evaporation temperature of 35 °C for 0.75 h. Then, acetic acid was added to the mixture. The solution was extracted and washed with ethyl ester for 4 times, the lower layer of yellow liquid was taken, and the ethyl acetate was removed by rotary evaporation. The rotary evaporation temperature was 45°C and the rotary evaporation time was 0.75h. The viscous yellow liquid was collected and dried. The long alkyl chain of the 1-allyl-3-dodecyl imidazolium salt prepared by this process was hydrophobic and could effectively repel moisture and improve the waterproof performance of the material. The cation of the imidazolium salt could combine with the cell membrane of the microorganism, destroy its structure and cause cell death, thereby having a strong spectrum antibacterial effect to obtain the imidazolium salt.

[0066] (2) Add 20.5 g of glycine to 200 mL of distilled water and mix them ultrasonically for 25 min. Then add molybdenum disulfide powder. The amount of molybdenum disulfide added is 1.5 g. Molybdenum disulfide can improve the barrier properties of materials such as polyvinyl alcohol and starch to water vapor, reduce the entry of water, and improve the tensile strength and toughness of the material, making it more durable. The nanosheet structure can directly destroy the bacterial cell membrane, causing the cell contents to leak, thereby killing the bacteria. Stir at 450 rpm for 18 h, then ultrasonically treat at 25 °C for 10 h, centrifuge, take the supernatant, add 5.0 g of glycine, ultrasonically treat for 5.5 h, and centrifuge for 60 min. During the centrifugation, replace the supernatant with distilled water every 10 min. Replacing the supernatant with the upper layer can better remove excess glycine in the solution, and collecting the precipitate for drying. Glycine can disrupt the permeability of bacterial cell membranes and can be incorporated into the peptidoglycan of bacterial cell walls to weaken its protective effect, thereby leading to cell death. The introduction of glycine also improves the interface bonding between molybdenum disulfide and the substrate, and enhances the mechanical properties of the film material. Molybdenum disulfide is stripped using glycine, so that the modified molybdenum disulfide nanosheets have better dispersibility and reduce the stacking phenomenon of nanosheets, thereby enhancing the mechanical properties, the contact area with bacteria and the antibacterial effect. However, the modification treatment of glycine also introduces hydrophilic groups, which is not conducive to maintaining the hydrophobic properties of molybdenum disulfide before modification, and glycine-modified molybdenum disulfide nanosheets are obtained;

[0067] (3) The imidazolium salt described in step (1) is dissolved in 20 mL of water, and then the glycine-modified molybdenum disulfide nanosheets described in step S2 are poured into the water. The mixture is placed in a magnetic stirrer, the temperature is controlled at 45°C, and the mixture is stirred at 50 rpm for 1.5 h. The imidazolium salt is adsorbed on the glycine-modified molybdenum disulfide nanosheets through π-π stacking and hydrogen bonding to form a sheet-like structure. The hydrophilic groups introduced by glycine are coated therein to exhibit excellent hydrophobic properties, and the antibacterial properties and mechanical properties are further enhanced. The mixture is then vacuum dried to obtain a multifunctional sheet-like filler.

[0068] This embodiment provides a method for preparing a waterproof and antibacterial polymer film material, which specifically includes the following steps:

[0069] S1. Stir 90 mL of anhydrous ethanol, 30 mL of distilled water, 5 mL of ammonia water and 0.6 mL of ethylenediamine thoroughly, heat to 37.5°C, add 1.2 g of 3-aminophenol, 2.8 mL of formaldehyde and 5.35 mL of ethyl orthosilicate in sequence, stir vigorously at 9000 rpm for 4 h, centrifuge, collect the precipitate, wash it twice with ethanol, vacuum dry it, and then place it in a muffle furnace and calcine it at 525°C for 4.5 h. Through this process, a silica nanoparticle with a fractal structure is prepared. The fractal rough surface can improve the adhesion of bacteria and has a larger surface area. As a carrier, it can load more active substances. In addition, the silica nanoparticles can fill the micropores and defects inside the material, improve the density and internal bonding force of the material, help to enhance the overall strength and toughness, and also help to reduce the entry of water to obtain a fractal nanocarrier;

[0070] S2, adding 1.0g of lignin to a eutectic of 100mL of water and tetrahydrofuran, wherein the volume ratio of water to tetrahydrofuran is 3:7, magnetic stirring for 0.75h, then dripping 40mL of deionized water into the lignin suspension at a rate of 2mL / min, stirring continuously for 3.5h, transferring to a dialysis bag, immersing the dialysis bag in excess deionized water to remove tetrahydrofuran, replacing deionized water every 12h, collecting the precipitate after 36h, and preparing nano-granular lignin by this process, which has a small particle size but a large specific surface area, increases the contact with other materials, improves the adsorption capacity, and obtains lignin nanoparticles;

[0071] S3. Grind the fractal nanocarrier described in step S1 and put it into a round-bottom flask, add 80 mL of toluene, ultrasonically treat for 25 minutes, then place it in an oil bath at 75°C, magnetically stir for 25 minutes, quickly add 0.3 mL of 3-aminopropyltriethoxysilane, react for 10 hours, centrifuge, wash the product with ethanol, and obtain a modified fractal nanocarrier, which is then dispersed in 30 mL of ultrapure water, ultrasonically treated for 20 minutes, add the lignin nanoparticles described in step S2, magnetically stir for 2.5 hours, and finally add silver nitrate in an amount of 9.0 mg. Silver nitrate has spectral antibacterial properties, and the antibacterial effect is long-lasting and effective. It can exert a strong antibacterial effect at low concentrations and has important application value in antibacterial materials. Stir in the dark at room temperature for 1.5 hours, drop 5 mL of 4% sodium borohydride aqueous solution liquid, reducing silver ions to form silver nanoparticles, centrifuging, washing, and vacuum drying. The introduction of 3-aminopropyltriethoxysilane improves the surface activity and loading stability of the fractal nanocarrier, and effectively improves the loading effect of lignin nanoparticles. The addition of lignin nanoparticles further enhances the adsorption and binding ability of the fractal nanocarrier to silver ions, and can load more silver nanoparticles, thereby better improving the antibacterial performance. The modified fractal nanocarrier adsorbs lignin nanoparticles and silver nanoparticles, forming a rougher spherical surface and presenting better waterproofness. The phenolic hydroxyl group of lignin can assist in reducing silver ions to silver nanoparticles, and the lignin nanoparticles can also reduce the agglomeration of silica particles, which is conducive to uniform dispersion, and more fully exerts the improvement effect of the filler on the mechanical properties, thereby obtaining a fractal spherical reinforcing filler.

[0072] S4. Mix starch and sodium periodate, the amount of starch added is 4.5g, the amount of sodium periodate added is 4.5g, add them into 100mL deionized water, use 0.4% hydrochloric acid solution to adjust the pH to 2.5, stir at 36.5℃ for 5.5h, then add 300mL anhydrous ethanol, stir evenly, centrifuge, take the precipitate, wash repeatedly with 75% ethanol solution until the pH is 7.0, then wash twice with distilled water, freeze-dry, and selectively oxidize the vicinal diol structure in starch by periodate to produce dialdehyde starch. The aldehyde group in the dialdehyde starch reacts with hydroxyl, amino and other groups in the material to form stable covalent bonds, thereby improving the mechanical strength of the material. At the same time, after cross-linking, the presence of hydrophilic groups is reduced, and the water resistance and waterproofness are enhanced to obtain a cross-linking agent;

[0073] S5, polyvinyl alcohol and corn starch are mixed at a mixing speed of 70 rpm and a mixing time of 25 min, and then a multifunctional flake filler, the fractal spherical reinforcing filler described in step S3, the cross-linking agent described in step S4 and glycerol are added at a mixing speed of 90 rpm and a mixing time of 25 min, and then the mixture is fed into a twin-screw extruder granulator with a length-to-diameter ratio of 40:1, and granulated at a temperature of 115°C. After granulation, the granulated material is added into a single-screw film blowing machine with a length-to-diameter ratio of 40:1, and plasticized, extruded, blown, cooled, and granulated at a temperature of 105°C in sequence. Rolling up, the multifunctional flake-like filler provides a larger surface area and enhances the interfacial interaction, and the fractal spherical reinforcing filler fills the gaps. The combination of the two optimizes the filling effect, and the addition of the cross-linking agent can not only undergo nucleophilic addition with the multifunctional flake-like filler, but also form coordination cross-linking with the fractal spherical reinforcing filler, and can also cross-link with the hydroxyl groups in polyvinyl alcohol and starch, so that the filler is fully compatible and dispersed in the matrix, the interface bonding between the materials is more firm, and defects are effectively reduced, thereby significantly improving the mechanical properties, waterproof properties and antibacterial properties, and obtaining a waterproof and antibacterial polymer film material.

[0074] Example 4

[0075] This embodiment proposes a waterproof and antibacterial polymer film material, including the following components in parts by weight: 30 parts of multifunctional flake-shaped filler, 10 parts of fractal spherical reinforcing filler, 10 parts of cross-linking agent, 40 parts of polyvinyl alcohol, 60 parts of corn starch, and 10 parts of glycerol.

[0076] The multifunctional sheet-like filler comprises the following components in parts by weight: 10 parts of glycine-modified molybdenum disulfide nanosheets and 40 parts of imidazolium salt.

[0077] The fractal spherical reinforcing filler comprises the following components in parts by weight: 20 parts of fractal nano-carriers, 5 parts of lignin nano-particles, and 10 parts of silver nitrate.

[0078] The preparation method of the multifunctional sheet-like filler specifically comprises the following steps:

[0079] (1) 5.0 g of 1-allylimidazole and 11.2 g of bromododecane were added to a stoppered conical flask in sequence, and 30 mL of acetonitrile was added as the reaction solvent. The bottle mouth was blocked with a rubber stopper and wrapped with plastic wrap and aluminum foil. The conical flask was placed in a constant temperature magnetic stirrer at 60 °C and 400 rpm for 24 h. After the reaction was completed, it was allowed to stand and cooled to room temperature. The reaction solvent acetonitrile was removed by rotary evaporation at 35 °C for 0.5 h. Then, acetic acid was added to the mixture. The solution was extracted and washed with ethyl ester for 5 times, the lower layer of yellow liquid was taken, and the ethyl acetate was removed by rotary evaporation. The rotary evaporation temperature was 45°C and the rotary evaporation time was 0.5h. The viscous yellow liquid was collected and dried. The long alkyl chain of 1-allyl-3-dodecyl imidazolium salt prepared by this process was hydrophobic and could effectively repel moisture and improve the waterproof performance of the material. The cation of the imidazolium salt could combine with the cell membrane of microorganisms, destroy its structure and cause cell death, thereby having a strong spectrum antibacterial effect to obtain the imidazolium salt.

[0080] (2) Add 20.0 g of glycine to 200 mL of distilled water and mix them ultrasonically for 20 min. Then add molybdenum disulfide powder. The amount of molybdenum disulfide added is 2.0 g. Molybdenum disulfide can improve the barrier properties of materials such as polyvinyl alcohol and starch to water vapor, reduce the entry of water, and improve the tensile strength and toughness of the material, making it more durable. The nanosheet structure can directly destroy the bacterial cell membrane, causing the cell contents to leak, thereby killing the bacteria. Stir at 500 rpm for 12 h, then ultrasonically treat at 25 °C for 8 h, centrifuge, take the supernatant, add 5.0 g of glycine, ultrasonically treat for 5 h, and centrifuge for 60 min. During the centrifugation, replace it with distilled water every 10 min. The supernatant can better remove excess glycine in the solution, collect the precipitate and dry it. Glycine can disrupt the permeability of bacterial cell membranes and can be incorporated into the peptidoglycan of bacterial cell walls to weaken its protective effect, thereby leading to cell death. The introduction of glycine also improves the interface bonding between molybdenum disulfide and the substrate, enhances the mechanical properties of the film material, and uses glycine to peel off molybdenum disulfide, so that the modified molybdenum disulfide nanosheets have better dispersibility and reduce the stacking phenomenon of nanosheets, thereby enhancing the mechanical properties, contact area with bacteria and antibacterial effect. However, the modification treatment of glycine also introduces hydrophilic groups, which is not conducive to maintaining the hydrophobic properties of molybdenum disulfide before modification, and obtains glycine-modified molybdenum disulfide nanosheets;

[0081] (3) The imidazolium salt described in step (1) is dissolved in 20 mL of water, and then the glycine-modified molybdenum disulfide nanosheets described in step S2 are poured into the water. The mixture is placed in a magnetic stirrer, the temperature is controlled at 50° C., and the mixture is stirred at 60 rpm for 1 hour. The imidazolium salt is adsorbed on the glycine-modified molybdenum disulfide nanosheets through π-π stacking and hydrogen bonding to form a sheet-like structure. The hydrophilic groups introduced by glycine are coated therein to exhibit excellent hydrophobic properties, and the antibacterial properties and mechanical properties are further enhanced. The mixture is then vacuum dried to obtain a multifunctional sheet-like filler.

[0082] This embodiment provides a method for preparing a waterproof and antibacterial polymer film material, which specifically includes the following steps:

[0083] S1. Stir 90 mL of anhydrous ethanol, 30 mL of distilled water, 5 mL of ammonia water and 0.6 mL of ethylenediamine thoroughly, heat to 40°C, add 1.2 g of 3-aminophenol, 2.8 mL of formaldehyde and 5.5 mL of ethyl orthosilicate in sequence, stir vigorously at 10,000 rpm for 3 h, centrifuge, collect the precipitate, wash it with ethanol 3 times, vacuum dry it, and then place it in a muffle furnace and calcine it at 550°C for 4 h. Through this process, a silica nanoparticle with a fractal structure is prepared. The fractal rough surface can improve the adhesion of bacteria and has a larger surface area. As a carrier, it can load more active substances. In addition, the silica nanoparticles can fill the micropores and defects inside the material, improve the density and internal bonding force of the material, help to enhance the overall strength and toughness, and also help to reduce the entry of water to obtain a fractal nanocarrier;

[0084] S2, adding 1.0g of lignin to a eutectic of 100mL of water and tetrahydrofuran, wherein the volume ratio of water to tetrahydrofuran is 3:7, magnetic stirring for 0.5h, then dripping 40mL of deionized water into the lignin suspension at a rate of 2mL / min, stirring continuously for 3h, transferring to a dialysis bag, immersing the dialysis bag in excess deionized water to remove tetrahydrofuran, replacing deionized water every 12h, collecting the precipitate after 36h, and preparing nano-granular lignin by this process, which has a small particle size but a large specific surface area, increases the contact with other materials, improves the adsorption capacity, and obtains lignin nanoparticles;

[0085] S3, grind the fractal nanocarrier described in step S1 and put it into a round-bottom flask, add 80 mL of toluene, ultrasonically treat for 20 minutes, then place it in an oil bath at 80°C, magnetically stir for 20 minutes, quickly add 0.1 mL of 3-aminopropyltriethoxysilane, react for 8 hours, centrifuge, wash the product with ethanol, and obtain a modified fractal nanocarrier, which is then dispersed in 30 mL of ultrapure water, ultrasonically treated for 10 minutes, add the lignin nanoparticles described in step S2, magnetically stir for 2 hours, and finally add silver nitrate in an amount of 10.0 mg. Silver nitrate has spectral antibacterial properties, and the antibacterial effect is long-lasting and effective. It can exert a strong antibacterial effect at low concentrations and has important application value in antibacterial materials. Stir for 1 hour in the dark at room temperature, drop 5 mL of a 6% sodium borohydride aqueous solution, The silver ions are reduced to form silver nanoparticles, centrifuged, washed, and vacuum dried. The introduction of 3-aminopropyltriethoxysilane improves the surface activity and loading stability of the fractal nanocarrier, and effectively improves the loading effect of the lignin nanoparticles. The addition of lignin nanoparticles further enhances the adsorption and binding ability of the fractal nanocarrier to silver ions, and can load more silver nanoparticles, thereby better improving the antibacterial performance. The modified fractal nanocarrier adsorbs lignin nanoparticles and silver nanoparticles, forming a rougher spherical surface and showing better waterproofness. The phenolic hydroxyl group of lignin can assist in reducing silver ions to silver nanoparticles, and the lignin nanoparticles can also reduce the agglomeration of silica particles, which is conducive to uniform dispersion, and more fully exerts the improvement effect of the filler on the mechanical properties, thereby obtaining a fractal spherical reinforcing filler.

[0086] S4. Mix starch and sodium periodate, with the amount of starch added being 5.0 g and the amount of sodium periodate added being 4.0 g, add them into 100 mL of deionized water, adjust the pH to 2.5 with a 0.4% hydrochloric acid solution, stir at 38°C for 5 h, then add 300 mL of anhydrous ethanol, stir evenly, centrifuge, take the precipitate, wash repeatedly with a 75% ethanol solution until the pH is 7.0, then wash twice with distilled water, freeze-dry, and selectively oxidize the vicinal diol structure in the starch with periodate to produce dialdehyde starch. The aldehyde group in the dialdehyde starch reacts with the hydroxyl group, amino group and other groups in the material to form a stable covalent bond, thereby improving the mechanical strength of the material. At the same time, after cross-linking, the presence of hydrophilic groups is reduced, and the water resistance and waterproofness are enhanced, thereby obtaining a cross-linking agent;

[0087] S5, polyvinyl alcohol and corn starch are mixed at a mixing speed of 80 rpm and a mixing time of 20 min, and then a multifunctional flake filler, the fractal spherical reinforcing filler described in step S3, the cross-linking agent described in step S4 and glycerol are added at a mixing speed of 100 rpm and a mixing time of 20 min, and then the mixture is sent to a twin-screw extruder granulator with a length-to-diameter ratio of 40:1, and granulated at a temperature of 120°C. After the granulation is completed, the granulated material is added to a single-screw film blowing machine with a length-to-diameter ratio of 40:1, and plasticized extrusion, inflation treatment, cooling, and film blowing are performed in sequence at a temperature of 110°C. Rolling up, the multifunctional flake-like filler provides a larger surface area and enhances the interfacial interaction, and the fractal spherical reinforcing filler fills the gaps. The combination of the two optimizes the filling effect, and the addition of the cross-linking agent can not only undergo nucleophilic addition with the multifunctional flake-like filler, but also form coordination cross-linking with the fractal spherical reinforcing filler, and can also cross-link with the hydroxyl groups in polyvinyl alcohol and starch, so that the filler is fully compatible and dispersed in the matrix, the interface bonding between the materials is more firm, and defects are effectively reduced, thereby significantly improving the mechanical properties, waterproof properties and antibacterial properties, and obtaining a waterproof and antibacterial polymer film material.

[0088] Comparative Example 1

[0089] This comparative example provides a waterproof and antibacterial polymer film material, which differs from Example 1 in that the multifunctional flake-shaped filler does not contain imidazolium salt; the preparation method of the multifunctional flake-shaped filler does not include steps (1) and (3); and the preparation method of the waterproof and antibacterial polymer film material is the same as that of Example 1.

[0090] Comparative Example 2

[0091] This comparative example provides a waterproof and antibacterial polymer film material, which differs from Example 1 in that the fractal spherical reinforcing filler does not contain lignin nanoparticles; the preparation method of the multifunctional sheet-like filler is the same as that of Example 1; and the preparation method of the waterproof and antibacterial polymer film material does not include step S2.

[0092] Comparative Example 3

[0093] This comparative example provides a waterproof and antibacterial polymer film material, which differs from Example 1 in that the waterproof and antibacterial polymer film material does not contain imidazolium salt, lignin nanoparticles and cross-linking agent; the preparation method of the multifunctional sheet-like filler does not include steps (1) and (3); and the preparation method of the waterproof and antibacterial polymer film material does not include steps S2 and S4.

[0094] Experimental Example 1

[0095] Mechanical properties test

[0096] Test sample: the waterproof and antibacterial polymer film material prepared in Examples 1-4 and Comparative Examples 1-3.

[0097] Test method: Using a universal testing machine, according to GB / T1040.1-2018 and GB / T228-2010, the test samples were cut into dumbbell-shaped (50mm×10mm×5mm) specimens with a cutter, and the tensile strength and elongation at break performance tests were carried out on the specimens at a tensile speed of 5mm / min. Each specimen was tested 3 times and the average value was taken.

[0098] Figure 2 The mechanical properties of Examples 1-4 and Comparative Examples 1-3 are shown in the figure. As shown in the figure, the tensile strength and elongation at break of Examples 1-4 are 44-50 MPa and 107-118%, respectively, indicating good mechanical properties. The tensile strength and elongation at break of Comparative Examples 1-3 are 25-36 MPa and 60-83%, respectively, indicating poor mechanical properties. The multifunctional sheet-like filler of Comparative Example 1 does not contain imidazolium salt, and the interface interaction between the filler and the matrix cannot be enhanced by electrostatic action, which is not conducive to enhancing the mechanical properties of the multifunctional sheet-like filler, resulting in poor mechanical properties. ; The fractal spherical reinforcing filler of comparative example 2 does not contain lignin nanoparticles, which is not conducive to the uniform dispersion of fractal nanocarriers, reduces the ability of the fractal spherical reinforcing filler to improve the mechanical properties, and results in poor mechanical properties; the waterproof and antibacterial polymer film material of comparative example 3 does not contain imidazolium salts, lignin nanoparticles and cross-linking agents, which not only limits the improvement effect of the multifunctional flake-shaped filler and the fractal spherical reinforcing filler on the mechanical properties, but also fails to make the interfaces of the components tightly and firmly bonded, which is not conducive to absorbing and dispersing impact force, increases the damage to the material caused by stress concentration, and results in poor mechanical properties.

[0099] Experimental Example 2

[0100] Waterproof performance test

[0101] Test sample: the waterproof and antibacterial polymer film material prepared in Examples 1-4 and Comparative Examples 1-3.

[0102] Test method: Use water vapor transmission rate tester (model W3 / 060) to test. Cut the test sample into a circle the size of a moisture permeable cup, place it in the moisture permeable cup with an appropriate amount of deionized water, seal the edge with a rubber ring, cover the moisture permeable cup and place it in the test chamber to start testing the water vapor transmission rate of the sample. Test 3 samples in each group and take the average value.

[0103] Figure 3 The water vapor transmission rate results of Examples 1-4 and Comparative Examples 1-3 are shown in the figure. As shown in the figure, the water vapor transmission rate of Example 1-4 is 2.182×10 -12 -2.301×10 -12 g cm / cm 2s·Pa, indicating strong waterproofness and not easy to absorb moisture; the water vapor permeability of comparative example 1-3 is 2.629×10 -12 -3.062×10 -12 g cm / cm 2 s·Pa, indicating that the waterproof property is weak and it is easy to absorb moisture; the multifunctional sheet block filler of comparative example 1 does not contain imidazolium salt, and cannot be adsorbed on the glycine-modified molybdenum disulfide nanosheets, so that the hydrophilic groups introduced by glycine cannot be coated therein, showing a certain hydrophilicity, resulting in weak waterproof property and easy to absorb moisture; the fractal spherical reinforcing filler of comparative example 2 does not contain lignin nanoparticles, which reduces the adsorption of silver nanoparticles and reduces the roughness of the spherical surface, resulting in weak waterproof property and easy to absorb moisture; the waterproof and antibacterial polymer film material of comparative example 3 does not contain imidazolium salt, lignin nanoparticles and cross-linking agent, which is not conducive to the waterproof ability of the double filler itself, and cannot make the two and other components firmly and tightly combined, which is not conducive to reducing the entry of water, resulting in weak waterproof property and easy to absorb moisture.

[0104] Experimental Example 3

[0105] Antibacterial performance test

[0106] Test sample: the waterproof and antibacterial polymer film material prepared in Examples 1-4 and Comparative Examples 1-3.

[0107] Test method: Before the test, use ultraviolet light to sterilize the environment. All test operations are carried out next to the flame of an alcohol lamp. Then pick up the pre-activated Escherichia coli and Staphylococcus aureus, add them to 1mL of sterile water, shake them thoroughly, dilute them, take 100μL of the diluted bacterial solution with a pipette, add it to the culture dish, spread the bacterial solution immediately with a spreader, pass the sterilized tweezers over the flame of the alcohol lamp, then use tweezers to clamp the sterilized test sample and stick it on the culture medium, press it lightly with tweezers, and immediately close the culture dish, set the temperature to 37℃ in a constant temperature incubator, and invert and culture for 24h. After the end, use the pouring method to determine the number of live bacteria and calculate the antibacterial rate (%).

[0108] Figure 4The antibacterial rate results of Examples 1-4 and Comparative Examples 1-3 are shown in the figure; as shown in the figure, the antibacterial rates of Escherichia coli and Staphylococcus aureus of Examples 1-4 are 99.99-99.99% and 99.98-99.99%, respectively, which are basically close to 100%, indicating that the antibacterial performance is good; the antibacterial rates of Escherichia coli and Staphylococcus aureus of Comparative Examples 1-3 are 63.78-85.35% and 54.83-80.36%, respectively, indicating that the antibacterial performance is general; the multifunctional sheet-shaped filler of Comparative Example 1 does not contain imidazolium salt, and cannot The spectral antibacterial property of imidazolium salt is brought into play, resulting in average antibacterial performance; the fractal spherical reinforcing filler of comparative example 2 does not contain lignin nanoparticles, which is not conducive to the adsorption and binding of more silver nanoparticles, resulting in average antibacterial performance; the waterproof antibacterial polymer film material of comparative example 3 does not contain imidazolium salt, lignin nanoparticles and cross-linking agent, which not only limits the antibacterial ability of the multifunctional flake filler and the fractal spherical reinforcing filler themselves, but also fails to make the fillers and other components firmly and tightly bonded, which is not conducive to reducing the growth space of bacteria, resulting in average antibacterial performance.

[0109] The above experimental results show that the mechanical properties, waterproof properties and antibacterial properties of Examples 1-4 of the present invention are significantly better than those of the samples of Comparative Examples 1-3. Among them, Example 1 using multifunctional flake block fillers and fractal spherical reinforcing fillers has better mechanical properties, better waterproof properties and better antibacterial properties. The multifunctional flake block fillers and fractal spherical reinforcing fillers are jointly filled in the matrix material of polyvinyl alcohol and corn starch. Under the further action of the cross-linking agent, the compatibility and dispersibility of the double fillers in the matrix material are improved, the filling effect is optimized, the interface bonding between the materials is more firmly and tightly bonded, which is helpful to absorb and disperse impact force, reduce the damage to the material caused by stress concentration, and also reduce the space for bacterial growth and the entry of moisture, thereby significantly improving the mechanical properties, waterproof properties and antibacterial properties of the film material.

[0110] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

[0111] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A waterproof and antibacterial polymer film material, characterized in that: The waterproof and antibacterial polymer film material comprises the following components in parts by weight: 20-30 parts of multifunctional flake block filler, 10-20 parts of fractal spherical reinforcing filler, 10-15 parts of cross-linking agent, 30-40 parts of polyvinyl alcohol, 50-60 parts of corn starch, and 5-10 parts of glycerol; the multifunctional flake block filler comprises the following components in parts by weight: 10-20 parts of glycine-modified molybdenum disulfide nanosheets and 30-40 parts of imidazolium salt; the fractal spherical reinforcing filler comprises the following components in parts by weight: 10-20 parts of fractal nanocarriers, 5-10 parts of lignin nanoparticles, and 8-10 parts of silver nitrate.

2. A method for preparing the waterproof and antibacterial polymer film material according to claim 1, characterized in that: The specific steps include: S1. 90 mL of anhydrous ethanol, 30 mL of distilled water, 5 mL of ammonia water and 0.6 mL of ethylenediamine were fully stirred and heated to 35-40°C. 1.2 g of 3-aminophenol, 2.8 mL of formaldehyde and 5.2-5.5 mL of ethyl orthosilicate were added in sequence. The mixture was vigorously stirred at a speed of 8000-10000 rpm for 3-5 h. The mixture was centrifuged to collect the precipitate, which was washed with ethanol for 2-3 times and dried in vacuo. The precipitate was then placed in a muffle furnace and calcined at 500-550°C for 4-5 h to obtain a fractal nanocarrier. S2, adding 1.0 g of lignin to a eutectic of 100 mL of water and tetrahydrofuran, wherein the volume ratio of water to tetrahydrofuran is 3:7, magnetically stirring for 0.5-1 h, then dripping 40 mL of deionized water into the lignin suspension at a rate of 2 mL / min, stirring continuously for 3-4 h, transferring to a dialysis bag, immersing the dialysis bag in excess deionized water to remove tetrahydrofuran, replacing deionized water every 12 h, collecting the precipitate after 36 h, and obtaining lignin nanoparticles; S3, grinding the fractal nanocarrier described in step S1 and placing it in a round-bottom flask, adding 80 mL of toluene, ultrasonically treating for 20-30 min, then placing it in an oil bath at 70-80°C, magnetically stirring for 20-30 min, quickly adding 0.1-0.5 mL of 3-aminopropyltriethoxysilane, reacting for 8-12 h, centrifuging, washing the product with ethanol to obtain a modified fractal nanocarrier, then dispersing it in 30 mL of ultrapure water, ultrasonically treating for 10-30 min, adding the lignin nanoparticles described in step S2, magnetically stirring for 2-3 h, and finally adding silver nitrate, stirring at room temperature in the dark for 1-2 h, dropping 5 mL of a 2-6% by mass sodium borohydride aqueous solution to reduce silver ions to form silver nanoparticles, centrifuging, washing, and vacuum drying to obtain a fractal spherical reinforcing filler; S4. Mix starch and sodium periodate, add to 100 mL of deionized water, adjust the pH to 2.5 with 0.4% hydrochloric acid solution, stir at 35-38°C for 5-6 hours, add 300 mL of anhydrous ethanol, stir evenly, centrifuge, take the precipitate, wash repeatedly with 75% ethanol solution until the pH is 7.0, then wash twice with distilled water, freeze-dry, and obtain a cross-linking agent; S5. Mix polyvinyl alcohol and corn starch at a mixing speed of 60-80rpm and a mixing time of 20-30min, then add the multifunctional flake filler, the fractal spherical reinforcing filler described in step S3, the cross-linking agent described in step S4 and glycerol at a mixing speed of 80-100rpm and a mixing time of 20-30min, and then feed into a twin-screw extruder granulator with a length-to-diameter ratio of 40:1, and granulate at a temperature of 110-120°C. After granulation, add the granulated material into a single-screw film blowing machine with a length-to-diameter ratio of 40:1, and perform plasticizing extrusion, blowing treatment, cooling and winding at a temperature of 100-110°C in sequence to obtain a waterproof and antibacterial polymer film material.

3. The method for preparing the waterproof and antibacterial polymer film material according to claim 2, characterized in that: In step S3, the amount of silver nitrate added is 8.0-10.0 mg.

4. The method for preparing the waterproof and antibacterial polymer film material according to claim 3, characterized in that: In step S4, the amount of starch added is 4.0-5.0 g, and the amount of sodium periodate added is 4.0-5.0 g.

5. The method for preparing the waterproof and antibacterial polymer film material according to claim 4, characterized in that: The method for preparing the multifunctional sheet-like filler specifically comprises the following steps: (1) 5.0 g of 1-allylimidazole and 11.2 g of bromododecane were added to a stoppered conical flask in sequence, 30 mL of acetonitrile was added as the reaction solvent, the bottle mouth was blocked with a rubber stopper and the bottle mouth was wrapped with plastic wrap and aluminum foil, the conical flask was placed in a constant temperature magnetic stirrer at a temperature of 50-60°C and a rotation speed of 200-400 rpm to react for 24 hours, after the reaction was completed, it was allowed to stand and cooled to room temperature, and the reaction solvent acetonitrile was removed by a rotary evaporator at a rotary evaporation temperature of 35°C and a rotary evaporation time of 0.5-1 hour, and then the solution was extracted and washed with ethyl acetate for 3-5 times, the lower layer of yellow liquid was removed, and the ethyl acetate was removed by rotary evaporation at a rotary evaporation temperature of 45°C and a rotary evaporation time of 0.5-1 hour, and the viscous yellow liquid was collected and dried to obtain an imidazolium salt; (2) Add 20.0-30.0 g of glycine to 200 mL of distilled water, ultrasonically mix for 20-30 min, then add molybdenum disulfide powder, stir at 400-500 rpm for 12-24 h, and then ultrasonically treat at 25 ° C for 8-12 h, centrifuge, take the supernatant, add 5.0 g of glycine, ultrasonically treat for 5-6 h, and centrifuge for 60 min. During the centrifugation, replace the supernatant with distilled water every 10 min to better remove excess glycine in the solution. Collect the precipitate and dry it to obtain glycine-modified molybdenum disulfide nanosheets; (3) Dissolve the imidazolium salt described in step (1) in 20 mL of water, then pour the glycine-modified molybdenum disulfide nanosheets described in step S2 into the water, place the mixture in a magnetic stirrer, control the temperature at 40-50° C., stir at 40-60 rpm for 1-2 h, and then vacuum dry to obtain a multifunctional sheet-like filler.

6. The method for preparing the waterproof and antibacterial polymer film material according to claim 5, characterized in that: In step (2), the amount of molybdenum disulfide added is 1.0-2.0 g.